2016
DOI: 10.3389/fpsyg.2016.00858
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Default System Functioning in Depression: Implications for Emotion Regulation

Abstract: Depression is widely seen as the result of difficulties in regulating emotions. Based on neuroimaging studies on voluntary emotion regulation, neurobiological models have focused on the concept of cognitive control, considering emotion regulation as a shift toward involving controlled processes associated with activation of the prefrontal and parietal executive areas, instead of responding automatically to emotional stimuli. According to such models, the weaker executive area activation observed in depressed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 94 publications
2
24
0
Order By: Relevance
“…Internal models play an active role in many human behaviours including visual attention 42 , higher cognitive functions such as memory and action planning 43 , decision making 44 and mental time travel 45 . Moreover, internal models are affected in mental disorders including major depression 46 , schizophrenia 47 and autism spectrum disorder 48,49 . Previous work has shown differences in the characteristics of line drawings made by schizophrenic patients 50 and in the ability of autistic children to predict objects from fragmented line drawings 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Internal models play an active role in many human behaviours including visual attention 42 , higher cognitive functions such as memory and action planning 43 , decision making 44 and mental time travel 45 . Moreover, internal models are affected in mental disorders including major depression 46 , schizophrenia 47 and autism spectrum disorder 48,49 . Previous work has shown differences in the characteristics of line drawings made by schizophrenic patients 50 and in the ability of autistic children to predict objects from fragmented line drawings 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The early growth and maturation of brain regions involved in self and social development (Pfeifer and Peake, 2012 ) is experience-dependent and requires nurturing self-other interactions in the context of attachment for developing the capacity to regulate cognitive and emotional states (Messina et al, 2016b ). For instance, a recent study (Brauer et al, 2016 ) indicated how 5-year old children exposed to higher maternal touch experiences show additional regional connectivity within the right dorso-medial prefrontal cortex and may benefit in terms of “social brain development.” In contrast, when an individual is denied these positive experiences, serious failures of self-development occur (Schore, 2005 ; Messina et al, 2016a ; Mucci, 2016 , 2018 ).…”
Section: Early Relational Experiences Attachment and The Developmentmentioning
confidence: 99%
“…On the other hand, difficulties in ER have been identified as putative risk and maintaining factors for several disorders ( Gratz et al, 2013 ). Poor emotion regulation has been linked to psychiatric disorders ( Barlow, 2002 ; Werner and Gross, 2010 ; Grecucci, 2012 ; Ehring, 2013 ; Mennin and Fresco, 2014 ; Messina et al, 2016a ), and more than 75% of psychiatric disorders are characterized by deficits in emotion regulation ( Kring and Werner, 2004 ). For example, anxiety, depression, and personality disorders are associated with specific dysregulated emotions ( Thayer and Lane, 2000 ; Mennin and Fresco, 2009 ; Schulze et al, 2011 ).…”
Section: Introduction: Regulating Emotions From Neuroscience To Psychmentioning
confidence: 99%